Feminist Manifesto or Hardcore Porn? Virginie Despentes's Transgression. (31st December 2012) - Edwards, Natalie
This article begins with a short overview of the recent phenomenon of erotic writing by French women authors, showing that transgression is becoming one of the hallmarks of women writers' and filmmakers' work. The article then concentrates on Virginie Despentes's essay King Kong Théorie (2006) and her most recent novel, Apocalypse Bébé (2011). I argue that King Kong Théorie is a provocative, self-reflexive and narcissistic text but that it ultimately opens French feminist theory to an anti-essentialist, anti-elitist readership. The article then analyses Despentes's most recent novel Apocalypse Bébé, which includes a series of female characters that each subvert stereotypes of female representation and broaden the text to a plurivocal expression of female subjectivity. Taken together, I show that these two texts – one theoretical and autobiographical, the other fictional — probe cultural and sexual taboos, question the boundaries of feminism, subvert a male point of view of sex and sexuality, and explore female erotic experience with shocking candour. Despentes's work, I argue, is part of a new French feminism that builds on the first- and second-wave feminist movements by confronting the reality of women's lived experience with the limits of representation of female experience.